3D hierarchically mesoporous Cu-doped NiO nanostructures as high-performance anode materials for lithium ion batteries. Issue 48 (16th November 2015) - Ma, Jingyun; Yin, Longwei; Ge, Tairu
Abstract : We report on the rational design and synthesis of three dimensional (3D) Cu-doped NiO architectures with an adjustable chemical component, surface area, and hierarchically porous structure as anodes for lithium ion battery. Abstract : We report on the rational design and synthesis of three-dimensional (3D) hierarchically mesoporous Cu-doped NiO architectures with an adjustable chemical component, surface area, and hierarchically porous structure. The effect of Mn doping and calcining temperature on the microstructure, surface area, and porous structure of the 3D mesoporous Cu-doped NiO nano-architectures is investigated using SEM, TEM, XPS, XRD, and nitrogen adsorption–desorption isotherm techniques. The electrochemical performance of the Cu-doped NiO architectures is studied via cyclic voltammetry (CV), galvanostatic charge–discharge and electrochemical impedance spectroscopy (EIS) techniques. The 3D hierarchically mesoporous Cu-doped NiO architectures display greatly enhanced electrochemical performance of high reversible capacity, high rate capability, and excellent cycling performance as LIB anode materials. The improved performance of 3D mesoporous Cu x NiO anodes can be attributed to the synergetic effects of an optimal level of Cu doping and the hierarchically porous feature. The doping of Cu greatly improves charge transport kinetics at the interface between the electrode and the electrolyte, and the hierarchically porous structure provides a larger surface area, allows effective electrolyte penetration, and alleviates the strain induced by volume excursion in cycle processes.